HIV-1 Antiretroviral Drug Resistance Mutations in Treatment Naïve and Experienced Panamanian Subjects: Impact on National Use of EFV-Based Schemes - Mendoza, Yaxelis (PLoS One, 2016)
The use of antiretroviral therapy in HIV infected subjects prevents AIDS-related illness and delayed occurrence of death. In Panama, rollout of ART started in 1999 and national coverage has reached 62.8% since then. The objective of this study was to determine the level and patterns of acquired drug resistance mutations of clinical relevance (ADR-CRM) and surveillance drug resistance mutations (SDRMs) from 717 HIV-1 pol gene sequences obtained from 467 ARV drug-experienced and 250 ARV drug-naïve HIV-1 subtypes B infected subjects during 2007–2013, respectively. The overall prevalence of SDRM and of ADR-CRM during the study period was 9.2% and 87.6%, respectively. The majority of subjects with ADR-CRM had a pattern of mutations that confer resistance to at least two classes of ARV inhibitors. The non-nucleoside reverse transcriptase inhibitor (NNRTI) mutations K103N and P225H were more prevalent in both ARV drug-naïve and ARV drug-experienced subjects. The nucleoside reverse transcriptase inhibitor (NRTI) mutation M184V was more frequent in ARV drug-experienced individuals, while T215YFrev and M41L were more frequent in ARV drug-naïve subjects. Prevalence of mutations associated to protease inhibitors (PI) was lower than 4.1% in both types of subjects. Therefore, there is a high level of resistance (>73%) to Efavirenz/Nevirapine, Lamivudine and Azidothymidine in ARV drug-experienced subjects, and an intermediate to high level of resistance (5–10%) to Efavirenz/Nevirapine in ARV drug-naïve subjects. During the study period, we observed an increasing trend in the prevalence of ADR-CRM in subjects under first-line schemes, but not significant changes in the prevalence of SDRM. These results reinforce the paramount importance of a national surveillance system of ADR-CRM and SDRM for national management policies of subjects living with HIV.